PENGEMBANGAN EMODUL MATEMATIKA BERBASIS KECERDASAN MAJEMUK UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS - Hasanah, Julia Fitrah (Jurnal Edukasi dan Penelitian Matematika, 2024)
Abstract The motivation behind this study is to decide the legitimacy of science e-modules in light of different insights to further develop the numerical critical thinking skill of grade VIII SMP/MTsN understudies. The subjects of this study were 31 grade VII understudies and one arithmetic teacher from SMPN 15 Padang. Information investigation methods are separated as per their stages, remembering for pleminary researc (fundamental investigation) information will be gotten from the outcomes of meetings as well as perceptions of quantitative information examination stages, to be specific diminishing information, introducing information and making inferences. Besides, for the consequences of item legitimacy information by specialists at the advancement stage, an investigation of the information got utilizing the Likert scale was done. The consequences of the review got the in general normal legitimacy of the emodule was 81.64% with a substantial class. The subtleties for material substance markers are 79.6% with legitimate classes, for show achievability markers 83.51% with substantial classifications, then, at that point, show practicality markers 82.11% with substantial classes, language pointers with a worth of 81.6%, at long last learning markers in view of different insights with a worth of 81.4% with legitimate classifications. In light of the clarification over, the compound insight based module to further develop the numerical critical thinking skill of grade VIII SMP/MTsN understudies.Keyword  - Emodule, Multiple Intelligence, Problem Solving